Fiber cement board with short linter fibers replacing wood pulp fibers and preparation method thereof
By using short lint fibers to replace wood pulp fibers in fiber cement boards, the problems of high price and unstable supply of wood pulp fibers are solved, and the effect of reducing production costs and environmental impacts is achieved, while maintaining high flexural strength.
Patent Information
- Application Number
- CN202411897119.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
High-quality wood pulp fibers are expensive and unstable in supply, resulting in high production costs and great environmental impact of fiber-reinforced cement boards.
Short cotton wool fibers were used to replace some wood pulp fibers, and by adjusting the formula and process steps, fiber cement boards with a density of 1.29-1.68kg/m3 and a flexural strength of 9.8-19.97MPa were prepared.
It significantly reduces production costs, reduces the consumption of forest resources and the environmental impact, while maintaining the flexural strength comparable to traditional products, meeting the high standards of the construction industry.
Smart Images

Figure BDA0005202153740000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber cement boards, and in particular relates to a fiber cement board in which short cotton linter fibers replace wood pulp fibers and a preparation method thereof. Background Art
[0002] In the construction industry, fiber-reinforced cement boards and fiber-reinforced calcium silicate boards are widely used building materials. Traditionally, the production formula of this type of board includes key components such as calcium materials (cement, lime, calcium carbide mud, etc.), silicon materials (quartz sand, silica powder, diatomaceous earth, fly ash, etc.), and fibers (wood pulp fibers, waste paper fibers, glass fibers, PVA fibers, etc.). Among them, high-quality wood pulp fibers suitable for the production of fiber-reinforced cement boards are mostly derived from coniferous species and are widely used due to their good reinforcing effect.
[0003] However, high-quality wood pulp fibers often need to be imported, and the price increase is large, and the supply chain is unstable, which has a great impact on sustainable production. Therefore, it has become a top priority to find a wood fiber substitute with lower cost and less environmental impact. Summary of the invention
[0004] In order to solve the problems raised by the background technology, the present invention provides a fiber cement board using short cotton linter fibers instead of wood pulp fibers and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] The present invention provides a fiber cement board in which short cotton linter fibers replace wood pulp fibers. The raw materials for preparing the fiber cement board include the following substances in percentage by mass:
[0007] Siliceous material 20%-80%, calcium material 10%-75%, short cotton linter fiber 1%-7%, wood pulp fiber 1%-9%, polyvinyl alcohol fiber 0-4%, auxiliary filler 0-30%;
[0008] The fiber cement board prepared from the raw materials has a density of 1.29-1.68 kg / m 3 , the flexural strength is 9.8-19.97MPa.
[0009] Furthermore, the raw materials of the fiber cement board include the following substances in percentage by mass:
[0010] Siliceous material 48%-78%, calcareous material 11%-41%, short cotton linter fiber 1%-4%, wood pulp fiber 1%-5%, polyvinyl alcohol fiber 0-3%, auxiliary filler 0-3%.
[0011] The present invention also provides a method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers, comprising the following steps:
[0012] (1) mixing a siliceous material, a calcareous material, short cotton linter fibers, wood pulp fibers, polyvinyl alcohol fibers, and auxiliary fillers to obtain a first slurry;
[0013] (2) the first slurry is dehydrated and then subjected to a molding process to obtain a first blank;
[0014] (3) After the first blank is stacked to a preset height, it is pressed and dehydrated to obtain a first slab;
[0015] (4) The first slab is subjected to pre-curing, demoulding, curing and drying in sequence to obtain a fiber cement board.
[0016] Furthermore, the addition ratio of the short cotton linter fiber to the wood pulp fiber is 0.65-1:1.
[0017] In the step (1), the solid content concentration of the first slurry is 15%-16%.
[0018] In the step (2), the thickness of the first blank is 9.4-9.6 mm.
[0019] In the step (3), the pressing and dehydration is performed at a pressure of 15-75 MPa and a continuous pressing time of 3-10 min.
[0020] In the step (4), the pre-curing temperature is 40-45° C. and the time is 10-14 hours.
[0021] In the step (4), the curing is autoclave curing or moisturizing curing. The temperature of autoclave curing is 180-185° C. and the time is 8-8.5 hours; the time of moisturizing curing is 27-28 days.
[0022] In the step (4), the drying is carried out at a temperature of 90-95° C. for 2-3 hours.
[0023] Beneficial Effects
[0024] The fiber cement board prepared by the present invention using short cotton linter fibers to replace part of the wood pulp fibers not only significantly reduces the production cost, reduces the consumption of forest resources and the impact on the environment, but also maintains the flexural strength equivalent to that of traditional products, meeting the high standards of the construction industry. DETAILED DESCRIPTION
[0025] The following examples are intended to illustrate the present invention rather than to further limit the present invention.
[0026] The present invention provides a fiber cement board in which short cotton linter fibers replace wood pulp fibers. The raw materials for preparing the fiber cement board include the following substances in percentage by mass:
[0027] Siliceous material 20%-80%, calcareous material 10%-75%, short cotton linter fiber 1%-7%, wood pulp fiber 1%-9%, polyvinyl alcohol fiber 0-4%, auxiliary filler 0-30%.
[0028] The price of wood pulp fiber is about 5,000 yuan / ton, and the price of cotton lint fiber is about 2,500-3,000 yuan / ton. Cotton lint fiber is used in the fiber raw materials of fiber cement board instead of wood pulp fiber to reduce production costs.
[0029] Among them, the calcareous material can be cement, lime, calcium carbide mud; the siliceous material can be quartz sand, silica powder, diatomaceous earth, fly ash. Short cotton lint fiber can be cotton lint solid waste generated in industrial production. In order to ensure the grinding effect, it can be pre-treated. For example, it can be soaked and dispersed with production water. As for production water, it is a solution with calcium hydroxide as the main component and a pH value of usually above 12 used in the production process of fiber cement board. Auxiliary fillers include flocculants, defoamers, color pastes, and sanding powders.
[0030] In order to further ensure the performance of the fiber cement board, such as density and flexural strength, preferably, the raw materials of the fiber cement board include the following substances in percentage by mass:
[0031] Siliceous material 48%-78%, calcareous material 11%-41%, short cotton linter fiber 1%-4%, wood pulp fiber 1%-5%, polyvinyl alcohol fiber 0-3%, auxiliary filler 0-3%.
[0032] Specifically, the fiber cement board is prepared by the following steps:
[0033] (1) Siliceous material, calcareous material, short cotton linter fiber, wood pulp fiber, polyvinyl alcohol fiber, and auxiliary filler are mixed to obtain a first slurry.
[0034] For example, after the raw materials are measured according to the set formula ratio, they are mixed in a homogenizer to achieve a solid content concentration of 15%-16% in the first slurry to meet production requirements.
[0035] The first slurry is placed or pumped into a slurry storage tank, and then placed into a headbox by gravity or pumping for production.
[0036] According to actual needs, vibrating screens and pulping equipment can be added to reprocess and select the first slurry before use.
[0037] (2) The first slurry is subjected to vacuum dehydration and then molding to obtain a first blank.
[0038] Specifically, the first slurry is dehydrated by the vacuum system while passing through the continuously running felt of the slurry flow main machine (for example, at a running speed of 85 m / min), and is wound on the forming cylinder into a blank. When the thickness of the blank reaches the set requirement, it is torn off.
[0039] Preferably, in step (2), the thickness of the first blank is 9.4-9.6 mm.
[0040] (3) After the first blank is stacked to a preset height, it is pressed and dehydrated to obtain a first slab.
[0041] During the stacking process, the first blank torn off the forming cylinder is trimmed and neatly stacked on a pad or a trolley, one plate and one mold at a time. For example, the stacking height does not exceed 1.1m, and the edge of the material and unqualified scraps are recycled.
[0042] The stacked slabs are sent to a press for pressing and dehydration according to process requirements. Preferably, in step (3), the pressing and dehydration pressure is 15-75 MPa, the continuous pressing time is 3-10 minutes, and a certain amount of water is discharged.
[0043] (4) The first slab is subjected to pre-curing, demoulding, curing and drying in sequence to obtain a fiber cement board.
[0044] First, the first slab is sent to a pre-curing kiln for heating and pre-curing. Preferably, the pre-curing temperature is 40-45° C. and the time is 10-14 hours.
[0045] Then, the pre-cured slab is separated from the steel formwork, the formwork is evenly brushed with an environmentally friendly release agent and returned to the stacking area for recycling; the slab is stacked on a trolley according to the process requirements and sent to the curing stage.
[0046] Among them, the curing is autoclave curing or moisturizing curing. Autoclave curing can be carried out in an autoclave at a temperature of 180-185°C for 8-8.5 hours, with a heating time of 2 hours and a cooling time of 2 hours; moisturizing curing can be carried out by covering the slab with felt with a certain water storage capacity for 27-28 days.
[0047] Finally, the cured board is dried. In the step (4), the drying temperature is 90-95° C. for 2-3 hours to ensure that the moisture content is less than 8.5%. After drying, the thickness is tested and the boards are classified and stacked.
[0048] In addition, it also includes cutting and sanding of fiber cement boards, mainly for cutting edges and corners, sanding the thickness to 8mm, and sanding the surface to 120 mesh to ensure that the surface is flat and flawless.
[0049] In the production process of fiber cement board, the production water is used to treat the fiber cement board and short cotton lint fiber. In order to meet the actual production needs, according to the configured pH detector, the tap water pipeline and the pH adjustment liquid pipeline are equipped with proportional regulating valves to adjust the proportion and realize the timely supply of production water.
[0050] The fiber cement board has a density of 1.29-1.68 kg / m 3 , the flexural strength is 9.8-19.97MPa.
[0051] The fiber cement board prepared by the present invention using short cotton linter fibers instead of wood pulp fibers not only significantly reduces production costs, reduces the consumption of forest resources and the impact on the environment, but also maintains a flexural strength comparable to that of traditional products, meeting the high standards of the construction industry.
[0052] Example 1
[0053] (1) 48% of siliceous material, 41% of calcareous material, 3% of short cotton linter fiber, 5% of wood pulp fiber, and 3% of auxiliary filler are mixed in a homogenizer for 15 minutes to obtain a first slurry.
[0054] (2) The first slurry is pumped to a slurry storage tank, diluted to a solid content concentration of 16%, pumped into a headbox, dehydrated by a vacuum system, and wound on a forming cylinder to form a blank. When the blank thickness reaches the set requirement, it is torn off to obtain the first blank. The thickness of the first blank is 9.5 mm.
[0055] (3) After the first blank is stacked to a length not exceeding 1.1 m, it is pressed and dehydrated to obtain a first slab. The pressing and dehydration process is performed at a pressure of 15 MPa and a continuous pressing time of 3 min.
[0056] (4) The first slab is pre-cured (temperature is 41°C, time is 12h), demolded, autoclaved (temperature is 180°C, time is 8.5h, heating time is 2h, cooling time is 4h), and dried (temperature is 90°C, time is 2.5h) to obtain a fiber cement board.
[0057] Example 2
[0058] (1) 48% of siliceous material, 41% of calcareous material, 4% of short cotton linter fiber, 4% of wood pulp fiber, and 3% of auxiliary filler are mixed in a homogenizer for 15 minutes to obtain a first slurry.
[0059] (2) The first slurry is pumped to a slurry storage tank, diluted to a solid content concentration of 16%, pumped into a headbox, dehydrated by a vacuum system, and wound on a forming cylinder to form a blank. When the blank thickness reaches the set requirement, it is torn off to obtain the first blank. The thickness of the first blank is 9.5 mm.
[0060] (3) After the first blank is stacked to a length not exceeding 1.1 m, it is pressed and dehydrated to obtain a first slab. The pressing and dehydration process is performed at a pressure of 15 MPa and a continuous pressing time of 3 min.
[0061] (4) The first slab is pre-cured (temperature is 41°C, time is 12h), demolded, autoclaved (temperature is 180°C, time is 8.5h, heating time is 2h, cooling time is 4h), and dried (temperature is 90°C, time is 2.5h) to obtain a fiber cement board.
[0062] Example 3
[0063] (1) 78% of siliceous material, 11% of calcareous material, 1% of short cotton linter fiber, 2% of wood pulp fiber, 3% of polyvinyl alcohol fiber, and 5% of auxiliary filler are mixed in a homogenizer for 15 minutes to obtain a first slurry.
[0064] (2) The first slurry is pumped to a slurry storage tank, diluted to a solid content concentration of 16%, pumped into a headbox, dehydrated by a vacuum system, and wound on a forming cylinder to form a blank. When the blank thickness reaches the set requirement, it is torn off to obtain the first blank. The thickness of the first blank is 9.8 mm.
[0065] (3) After the first blank is stacked to a length not exceeding 1.1 m, it is pressed and dehydrated to obtain a first slab. The pressing and dehydration process is performed at a pressure of 75 MPa and a continuous pressing time of 10 min.
[0066] (4) The first slab was subjected to pre-curing (temperature of 41°C, time of 12 hours), demoulding, and moisture-curing (28 days) to obtain a fiber cement board.
[0067] Example 4
[0068] (1) 78% of siliceous material, 11% of calcareous material, 2% of short cotton linter fiber, 1% of wood pulp fiber, 3% of polyvinyl alcohol fiber, and 5% of auxiliary filler are mixed in a homogenizer for 15 minutes to obtain a first slurry.
[0069] (2) The first slurry is pumped to a slurry storage tank, diluted to a solid content concentration of 16%, pumped into a headbox, dehydrated by a vacuum system, and wound on a forming cylinder to form a blank. When the blank thickness reaches the set requirement, it is torn off to obtain the first blank. The thickness of the first blank is 9.8 mm.
[0070] (3) After the first blank is stacked to a length not exceeding 1.1 m, it is pressed and dehydrated to obtain a first slab. The pressing and dehydration process is performed at a pressure of 75 MPa and a continuous pressing time of 10 min.
[0071] (4) The first slab was subjected to pre-curing (temperature of 41° C., time of 12 h), demoulding, and moisture-curing (27 days) to obtain a fiber cement board.
[0072] Comparative Example 1
[0073] Compared with Example 1, short cotton linter fibers are not added in step (1), and the addition amount of wood pulp fibers is 8%. The remaining operations are the same as those in Example 1, and the same raw materials and addition amounts are used.
[0074] Comparative Example 2
[0075] Compared with Example 3, short cotton linter fibers are not added in step (1), and the addition amount of wood pulp fibers is 3%. The remaining operations are the same as those of Example 3, and the same raw materials and addition amounts are used.
[0076] The siliceous material in the above embodiments and comparative examples is quartz sand, and the calcareous material is cement. In addition, the short cotton lint fibers in the embodiments of the present invention are degreased before preparing the fiber cement board. The specific degreasing method is as follows: send the cotton lint to be treated with an oil content of 3%-4% (actual measurement) into a crusher, add the first fiber cement board production water, the amount of the first fiber cement board production water added is 2.5 times the weight of the cotton lint to be treated, and crush for 15 minutes at a speed of 600rpm in the crusher; the crushed cotton lint is placed in a circulating water tank, and mixed according to the ratio of the weight of the crushed cotton lint to the amount of the first fiber cement board production water added of 1:4.5, the pH of the first fiber cement board production water is 11.5, and the temperature is 35°C. Stir once every 30 minutes, and stir for 5 minutes each time. Detect the pH value after each stirring. If it is lower than 11.0, add the third fiber cement board production water, and the pH of the third fiber cement board production water is not lower than 12. When the total reaction time reaches 6 hours, the cotton lint fiber no longer has obvious signs of floating, and the degreasing is completed. Since both the short cotton lint fiber and the wood pulp fiber are lightweight materials, the short cotton lint fiber after degreasing can be premixed with the wood pulp fiber (all or at least part) before being injected into the homogenizer. The premixing can be carried out by combining high-pressure gas delivery with cyclone stirring. The wood pulp fiber is sent into the short cotton lint fiber slurry stirred by the cyclone under high-pressure gas blowing, and then sent to the homogenizer together after stirring.
[0077] Experimental Results
[0078] The fiber cement boards prepared in Examples 1-4, Comparative Example 1 and Comparative Example 2 were tested for density and flexural strength, specifically according to the testing method in GBT 7019-2014. The test results are shown in Table 1.
[0079] Table 1 Test results
[0080]
[0081] It can be seen from Table 1 that, compared with Comparative Example 1 and Comparative Example 2, the fiber cement boards prepared by the present application in Examples 1-4 maintain a flexural strength comparable to that of traditional products and meet the high standards of the construction industry.
Claims
1. A fiber cement board using short cotton linter fibers instead of wood pulp fibers, characterized in that: The raw materials for preparing the fiber cement board include the following substances in percentage by mass: Siliceous material 30%-80%, calcium material 10%-50%, short cotton linter fiber 1%-7%, wood pulp fiber 1%-9%, polyvinyl alcohol fiber 0-4%, auxiliary filler 0-30%; The fiber cement board prepared from the raw materials has a density of 1.29-1.68 kg / m 3 , the flexural strength is 9.8-19.97MPa.
2. The fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 1, characterized in that: The raw materials for preparing the fiber cement board include the following substances in percentage by mass: Siliceous material 48%-78%, calcareous material 11%-41%, short cotton linter fiber 1%-4%, wood pulp fiber 1%-5%, polyvinyl alcohol fiber 0-3%, auxiliary filler 0-5%.
3. A method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) mixing a siliceous material, a calcareous material, short cotton linter fibers, wood pulp fibers, polyvinyl alcohol fibers, and auxiliary fillers to obtain a first slurry; (2) the first slurry is dehydrated and then subjected to a molding process to obtain a first blank; (3) After the first blank is stacked to a preset height, it is pressed and dehydrated to obtain a first slab; (4) The first slab is subjected to pre-curing, demoulding, curing and drying in sequence to obtain a fiber cement board.
4. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: The addition ratio of the short cotton linter fiber to the wood pulp fiber is 0.65-1:
1.
5. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (1), the solid content concentration of the first slurry is 15%-16%.
6. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (2), the thickness of the first blank is 9.4-9.6 mm.
7. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (3), the pressing and dehydration is performed at a pressure of 15-75 MPa and a continuous pressing time of 3-10 min.
8. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (4), the pre-curing temperature is 40-45° C. and the time is 10-14 hours.
9. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (4), the curing is autoclave curing or moisturizing curing. The temperature of autoclave curing is 180-185° C. and the time is 8-8.5 hours; the time of moisturizing curing is 27-28 days.
10. The method for preparing a fiber cement board using short cotton linter fibers instead of wood pulp fibers according to claim 3, characterized in that: In the step (4), the drying is carried out at a temperature of 90-95° C. for 2-3 hours.
Citation Information
Patent Citations
Environment-friendly type water cinder calcium silicate plate and preparation
CN101209912A
Light-weight calcium silicate plate and preparation method thereof
CN103449773A
Diatomite-based cement board and manufacturing method thereof
CN103880349A
External wall thermal insulation board and preparation method thereof
CN107117929A
Absorbent cotton gauze to promote wound healing
CN109125788A